Regulation of phospholipid synthesis in phosphatidylserine synthase-deficient (chol) mutants of Saccharomyces cerevisiae. - Letts, V A (1985)
chol mutants of Saccharomyces cerevisiae are deficient in the synthesis of the phospholipid phosphatidylserine owing to lowered activity of the membrane-associated enzyme phosphatidylserine synthase. chol mutants are auxotrophic for ethanolamine or choline and, in the absence of these supplements, cannot synthesize phosphatidylethanolamine or phosphatidylcholine (PC). We exploited these characteristics of the chol mutants to examine the regulation of phospholipid metabolism in S. cerevisiae. Macromolecular synthesis and phospholipid metabolism were examined in chol cells starved for ethanolamine. As expected, when chol mutants were starved for ethanolamine, the rates of synthesis of the phospholipids phosphatidylethanolamine and PC declined rapidly. Surprisingly, however, coupled to the decline in PC biosynthesis was a simultaneous decrease in the overall rate of phospholipid synthesis. In particular, the rate of synthesis of phosphatidylinositol decreased in parallel with the decline in PC biosynthesis. The results obtained suggest that the slowing of PC biosynthesis in ethanolamine-starved chol cells leads to a coordinated decrease in the synthesis of all phospholipids. However, under conditions of ethanolamine deprivation in chol cells, the cytoplasmic enzyme inositol-1-phosphate synthase could not be repressed by exogenous inositol, and the endogenous synthesis of the phospholipid precursor inositol appeared to be elevated. The implications of these findings with respect to the coordinated regulation of phospholipid synthesis are discussed.